Fucana ativa via das Map quinases e inibe a proliferação de células de ovário de hamster chinês (CHO) - Nobre, Leonardo Thiago Duarte Barreto (2011)
Fucan is a term used to denominate L-fucose rich sulfated polysaccharides. The fucans have been studied due their pharmacological activities like antithrombotic, antiproliferative and antioxidant. We have extracted three fucan fractions from the brown seaweed Spatoglossum schröederi. These fucans were denominated Fuc B 1, Fuc B 1.5 and Fuc B 2. The chemical analyzes show that the fucans have very similar composition as demonstrated by agarose electrophoresis gel, sugar and sulfate content. The antiproliferative effect was determined by MTT and BrdU methodologies in CHO cells. The inhibition of proliferation effect of the three fractions was about 40%. Therefore this we proceed just with the Fuc B 2 due the higher yield. There is no apoptosis indication using the anexin V/propidium iodide test. We found a cell cycle phase G1 arrest. The western blotting show that the PKC; pFAK; pERK 1/2 are activated when the cells were treated with fucans. The treatement with inhibitor of MAPK PD98059 extinguished the fucan effect. These results indicates that fucan act by the ERK pathway inducing the cell death.